2014
DOI: 10.1097/jom.0000000000000323
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Observational Studies of the Association Between Chronic Occupational Exposure to Lead and Amyotrophic Lateral Sclerosis

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 80 publications
1
38
1
Order By: Relevance
“…Finally, only one of the 16 meta-analyses (exposure to lead [33] ) presented convincing evidence for an association with ALS, supported by more than 1,000 cases, p < 0.001 under the random-effects model, small or moderate heterogeneity (I 2 <50%), a 95% PI excluding the null value, absence of evidence for small-study effects and excess statistical significance. This association had a summary OR of 1.81 (95% CI 1.39-2.35; p = 2.13 × 10 -6 ) with small heterogeneity (I 2 = 12.7%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, only one of the 16 meta-analyses (exposure to lead [33] ) presented convincing evidence for an association with ALS, supported by more than 1,000 cases, p < 0.001 under the random-effects model, small or moderate heterogeneity (I 2 <50%), a 95% PI excluding the null value, absence of evidence for small-study effects and excess statistical significance. This association had a summary OR of 1.81 (95% CI 1.39-2.35; p = 2.13 × 10 -6 ) with small heterogeneity (I 2 = 12.7%).…”
Section: Resultsmentioning
confidence: 99%
“…Five were significant at p < 0.001 under the randomeffects model ( table 1 ): farming [32] , lead [33] , n-3 fatty acids [34] , pesticides [32] and serum uric acid [35] . The heterogeneity was large (I 2 ≥ 50 and ≤ 75%) in 5 metaanalyses and very large (I 2 >75%) in 3 meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Whites, males, non-Hispanics, those aged >60 years, and those with a family history of the disease are more likely to develop ALS (1,6). Previous exposure to heavy metals (e.g., lead and chromium), pesticides, and ß-N-methylamino-L-alanine (BMAA) produced by cyanobacteria also have been associated with an increased risk for ALS (7)(8)(9)(10)(11). Military service continues to be a possible risk factor for ALS; however, no strong evidence has been found linking etiology with service (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Occupational exposure to lead has been found to be associated with the occurrence of ALS. According to Wang et al [40], the risk of developing ALS almost doubled among individuals with a history of exposure to lead, with a pooled odds ratio of 1.81 (95% CI 1.39–2.36). Santurtún et al [11] found higher mortality ratios for people older than 65 years in the provinces of northern Spain.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the exposure to metals, systematic evidence includes mostly lead [22, 23, 40, 41], but also iron, selenium, manganese [22, 41], mercury [41] and aluminium [26]. Occupational exposure to lead has been found to be associated with the occurrence of ALS.…”
Section: Introductionmentioning
confidence: 99%